Extraction and Characterization of Phenolic Compounds from the Stem Bark of Sonneratia caseolaris (Lythraceae) and Their Potential Antibacterial Activity - Harizon, Harizon; Kurnia, Dikdik; Sumiarsa, Dadan; Herlina, Tati; Sinaga, Siska Elisahbet; Shiono, Yoshihito; Azmi, Mohamad Nurul; Supratman, Unang (Indonesian Journal of Chemistry, 2025)
The ethyl acetate fraction separated from the stembark of Sonneratia caseolaris retrieved three phenolic compounds, including quercetin-3-O-glucoside (1), quercetin (2), and 1-O-(2,4-dihydroxybenzoyl)-β-D-glucopyranose (3). For the first time, compounds 1 and 3 were discovered from Sonneratia genus. Data from various spectroscopic techniques, including mass spectroscopy and one- and two-dimensional NMR, were used to identify their chemical structures. Antibacterial activity has also been assessed for all compounds against Staphylococcus aureus ATCC 25175 and Streptococcus mutans ATCC 6538. Compounds 1–3 displayed varying levels of antibacterial activity against S. aureus and S. mutans. However, all compounds exhibited lower efficacy compared to the control, with their minimum inhibitory concentration (MIC) values ranging from 71.25 to greater than 100 µg/mL. This study provides a foundation for optimizing S. caseolaris phenolic compounds as antibacterial agents and highlights the need for comparative studies within the Sonneratia genus to identify potent bioactive candidates through structural modification or synergistic approaches.